1999
DOI: 10.1115/1.555442
|View full text |Cite
|
Sign up to set email alerts
|

Flowfield Measurements for a Highly Turbulent Flow in a Stator Vane Passage

Abstract: Turbine vanes experience high convective surface heat transfer as a consequence of the turbulent flow exiting the combustor. Before improvements to vane heat transfer predictions through boundary layer calculations can be made, we need to understand how the turbulent flow in the inviscid region of the passage reacts as it passes between two adjacent turbine vanes. In this study, a scaled-up turbine vane geometry was used in a low-speed wind tunnel simulation. The test section included a central airfoil with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Several efforts were made previously to understand the contributions of high freestream Tu and Re on timeaveraged endwall heat transfer in gas turbine vanes ( [15], [16]). Blair [12] and Dunn et al [13] were among the initial researchers who investigated the endwall heat flux rates between turbine cascade blades and reported an increase by a factor of 3 near the leading edge of endwall and turbine junction.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Several efforts were made previously to understand the contributions of high freestream Tu and Re on timeaveraged endwall heat transfer in gas turbine vanes ( [15], [16]). Blair [12] and Dunn et al [13] were among the initial researchers who investigated the endwall heat flux rates between turbine cascade blades and reported an increase by a factor of 3 near the leading edge of endwall and turbine junction.…”
Section: Previous Studiesmentioning
confidence: 99%
“…As the now passes the downstream turbine vane passage, the turbulence level still remains high [4]. Porreca et al [5] measured the time average turbulence level which reaches a level up to 14% in the core of the secondary flows and the wake of the exit of the second stator.…”
Section: Introductionmentioning
confidence: 97%
“…Oldfield (1992, 1996) and the previous work by Holmberg (1996) and Holmberg and Pestian (1996) are the exceptions. Giel, et al (2000) Low speed 0.11 18% Barringer, et al (2002) Low speed 0.43 18% Wang, et al (1998) Low speed -20% Thole, et al (1994) Low speed 0.11 13% Low speed -10% Boyle, et al (1998) Low speed -17% Schauer and Pestian (1996) Low speed -20% Radomsky and Thole (2000) Transonic <0.1 5% Holmberg (1996) Low speed -13% Mehendale and Han (1992) …”
Section: Time-resolved Heat Transfermentioning
confidence: 99%
“…The streamwise velocity fluctuations (u') were shown to decrease through the blade passage, while cross-stream (v') and lateral (w') fluctuations increased. Detailed measurements using a 3 component LDV system were reported in Radomsky and Thole (2000) and showed that turbulence remains quite high throughout the passage. Length scale was shown to decrease through the blade passage, although not considerably.…”
Section: Introductionmentioning
confidence: 99%